Ultra‐Smooth, Chemically Functional Silica Surfaces for Surface Interaction Measurements and Optical/Interferometry‐Based Techniques. Issue 2 (30th October 2017) - Dobbs, Howard A.; Kaufman, Yair; Scott, Jeff; Kristiansen, Kai; Schrader, Alex M.; Chen, Szu‐Ying; Duda, Peter; Israelachvili, Jacob N.
Abstract : The study of interfacial phenomena is central to a range of chemical, physical, optical, and electromagnetic systems such as surface imaging, polymer interactions, friction/wear, and ion‐transport in batteries. Studying intermolecular forces and processes of interfaces at the sub‐nano scale has proven difficult due to limitations in surface preparation methods. Here, we describe a method for fabricating reflective, deformable composite layers that expose an ultra‐smooth silica (SiO2 ) surface (RMS roughness < 0.4 nm) with interferometric applications. The robust design allows for cleaning and reusing the same surfaces for over a week of continuous experimentation without degradation. The electric double‐layer forces measured using the composite surfaces are within 10% of the theoretically predicted values. We also demonstrate that standard chemisorption and physisorption procedures on silica can be applied to chemically modify the surfaces; as a demonstration of this, the composite surfaces are successfully modified with octadecyltrichlorosilane (OTS) to study their hydrophobic interactions in water using a surface force apparatus (SFA). These composite surfaces provide a basis for the preparation of a variety of new surfaces, and should be particularly beneficial for the SFA and colloidal probe methods that employ optical/interferometric and electrochemical techniques, enabling characterization of previously unattainable surface and interfacial phenomena. Abstract : The fabrication of composite surfaces comprising a surface silica layer with sub‐nanometer RMS roughness capable of measuring surface forces with high accuracy and precision using the SFA is reported. The composite surfaces can be modified using various deposition, reaction, and adsorption methods to enable characterization of previously unattainable surface and interfacial phenomena beneficial to SFA and colloidal probe techniques.